2013
DOI: 10.1155/2013/237581
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Interfering Substances on the Antimicrobial Activity of Selected Quaternary Ammonium Compounds

Abstract: Standard cleaning processes may not remove all the soiling typically found in food industry, such as carbohydrates, fats, or proteins. Contaminants have a high impact in disinfection as their presence may reduce the activity of disinfectants. The influence of alginic acid, bovine serum albumin, yeast extract, and humic acids was assessed on the antimicrobial activities of benzalkonium chloride and cetyltrimethyl ammonium bromide against Bacillus cereus vegetative cells and Pseudomonas fluorescens. The bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 55 publications
1
37
1
Order By: Relevance
“…Numerous studies have confirmed that organic matter interferes with the activity of antimicrobials [36,37,38]. The interaction between organic matter and antimicrobial substance leads to reduced antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have confirmed that organic matter interferes with the activity of antimicrobials [36,37,38]. The interaction between organic matter and antimicrobial substance leads to reduced antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…This will be investigated in future work. Likewise, Fujishima et al (2000) state that photocatalysts are not especially useful at breaking down large volumes of soilage, but they are capable of destroying it as it accumulates, and Araújo et al (2013) report on how, in the presence of interfering substances, the antimicrobial effectiveness of quaternary ammonium compounds was reduced and depended on the type of interfering substance. To the authors' knowledge, no other reports have been published specifically relating to the effect a brewery soil on a TiO 2 -Mo photocatalytic surface has on microbial numbers.…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration in the strict compliance of these recommendations is the finding in several studies that interfering substances (including body secretions) could have a strong impact on the efficiency of a disinfectant (27, 28). To simulate clean/dirty environments, standardized interfering substances are used to evaluate disinfection product efficiency according to Phase 2 EN standards.…”
Section: Introductionmentioning
confidence: 99%